Role of Mesencephalic Astrocyte-Derived Neurotrophic Factor in Alcohol-Induced Liver Injury - Chhetri, Goma (Oxid Med Cell Longev, 2020)
Consumption of alcohol in immoderate quantity induces endoplasmic reticulum (ER) stress response (alcohol-induced ER stress). Mesencephalic astrocyte-derived neurotrophic factor (MANF), an ER stress-inducible protein, works as an evolutionarily conserved regulator of systemic and liver metabolic homeostasis. In this study, the effects of MANF on alcohol-induced liver injury were explored by using hepatocyte-specific MANF-knockout mice (MANF(ΔHep)) in a chronic-plus-binge alcohol feeding model. We found that alcohol feeding upregulated MANF expression and MANF(ΔHep) mice exhibited more severe liver injury with extra activated ER stress after alcohol feeding. In addition, we found that MANF deficiency activated iNOS and p65 and increased the production of NO and anti-inflammatory cytokines, which was further enhanced after alcohol treatment. Meanwhile, MANF deletion upregulated the levels of CYP2E1, 4-HNE, and MDA and downregulated the levels of GSH and SOD. These results indicate that MANF has potential protection on alcohol-induced liver injury, and the underlying mechanisms may be associated with meliorating the overactivated ER stress triggered by inflammation and oxidative stress via inhibiting and reducing NO/NF-κB and CYP2E1/ROS, respectively. Therefore, MANF might be a negative regulator in alcohol-induced ER stress and participate in the crosstalk between the NF-κB pathway and oxidative stress in the liver. Conclusions. This study identifies a specific role of MANF in alcohol-induced liver injury, which may provide a new approach for the treatment of ALI.